Women's empowerment and gender equality programs to support stunting elimination in South Central Timor Regency - Djogo, Herliana Monika Azi; Letor, Yulia M.K; Gatum, Angela Muryati; Dion, Yohanes (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2024)
Introduction: Stunting remains a significant public health concern in Indonesia, particularly in East Nusa Tenggara Province, where it is the most prevalent among all Indonesian provinces at about 42.6 per cent. Empowerment initiatives represent a crucial approach to addressing this issue. Women's empowerment holds profound significance as it governs and nurtures human resources within the household, especially children, who represent the nation's future generation. This community service aims to implement a women's empowerment program by establishing a group of Women Providing Health Information (Perempuan Pemberi Informasi Kesehatan) and enhancing women's access to national health services. Methods: We conducted an experimental quantitative study involving mothers with children aged 12 to 59 months. Inclusion criteria included mothers with children aged 12 to 59 months residing in Kesetnana Village. Data were analyzed using the Wilcoxon test. The mothers' classes aimed to enhance mothers' knowledge regarding the first 1000 days of life and the nutritional requirements during this period. The study included 35 participants, with the questionnaire on stunting knowledge serving as the primary instrument. Results: The findings revealed a notable increase in participant knowledge in the post-test compared to the pre-test, with a mean rank of 88.00 and a p-value of 0.000. Conclusions: The results underscore the continued need for a gender- and culture-based approach to health promotion to mitigate the incidence of stunting. Effective health education on stunting reduction requires collaborative efforts between health workers and local communities, with mutual support being essential.